MODEL KEPEMIMPINAN ADAPTIF DAN PARTISIPATIS KEPALA SEKOLAH DALAM LEMBAGA SEKOLAH - Fauzan, Moch.FikriF; Abdul Malik Romadhon; Machdum Bachtiar; Eneng Muslihah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the roles of adaptive and participative leadership of school principals and their correlation in improving educational quality Adaptive leadership plays a central role in addressing policy dynamics, societal changes, and the increasingly complex needs of students by emphasizing vision, collaboration, and a culture of continuous learning Meanwhile, participative leadership focuses on involving teachers, staff, students, and parents in decision-making, planning, and school program implementation, thereby fostering a democratic, inclusive, and collaborative environment The findings indicate that adaptive leadership functions as a macro strategy for managing change, while participative leadership serves as a micro strategy to ensure the active participation of all stakeholders Both leadership models are integrative and complementary, creating innovative, democratic, and competitive schools capable of responding to the challenges of the disruption era